Workplace wars and how to end them : turning personal conflicts into productive teamwork - Kaye, Kenneth (American Management Association, 1994)
Is your workplace toxic with grudges, petty sniping, or not-so-petty vendettas? Do infighting and backstabbing eat away at productivity? Are turf battles rampant? Are underground issues blocking the chance for teamwork? Every workplace has its disagreements and always will. But disruptive conflicts can and should be resolved if the organization and the individuals involved are to move forward. In this immensely helpful guide, business psychologist Kenneth Kaye shows how to build the kind of teamwork that recognizes conflict quickly, deals with it constructively, and parlays it expertly into creativity and growth. Kaye provides a consistent system - not a random bunch of "feel-good" quick fixes - for managing conflict among people who must work together closely